A silicon-carbon composite material and its preparation method and application

By preparing silicon-carbon composite materials in lithium-ion batteries and using nanocellulose to generate carbon fiber layer to coat silicon-based materials, the problem of poor circulation performance of silicon-based materials in lithium-ion batteries is solved, and higher circulation stability is achieved. Conductive properties.

CN114824234BActive Publication Date: 2025-02-25BLUE OCEAN & BLACK STONE TECH CO LTD (FUJIAN)
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210613164.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-02-25
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing silicon-based materials have poor circulation performance in lithium-ion batteries due to low electronic conductivity and large volume changes.

Method used

Silicon-carbon composite material is prepared by mixing the nanocellulose solution, silicon source and coupling agent and calcining it, in which the nanocellulose is coated on the surface of the silicon-based material by carbonization, and the volume expansion is buffered.

Benefits of technology

It improves the cyclic stability of silicon-carbon composite materials, enhances the conductivity, and reduces the negative impact of volume expansion on battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114824234B_ABST
    Figure CN114824234B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of lithium battery technology, and specifically relates to a silicon-carbon composite material, a preparation method thereof, and an application thereof. The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps: mixing a nanocellulose solution, a silicon source, and a coupling agent, and then calcining to obtain the silicon-carbon composite material. The present invention combines nanocellulose and a silicon source through a coupling agent, so that the nanocellulose can be tightly wrapped on the surface of the silicon source. During the calcination process, the nanocellulose is carbonized to generate a carbon fiber layer, which is coated on the surface of the silicon-based material. It can play a good buffering role during the charge and discharge process, reduce the impact of the volume expansion of the silicon-based material, and improve the cycle stability of the silicon-carbon composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries mainly consist of a positive electrode, an electrolyte, and a negative electrode, and they work mainly by the movement of lithium ions between the positive and negative electrodes. During the charge and discharge process, lithium ions are intercalated and deintercalated back and forth between the two electrodes: when charging, lithium ions are deintercalated from the positive electrode and intercalated into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge.

[0003] Negative electrode materials are an important component of lithium-ion batteries and directly affect the electrochemical performance of lithium-ion batteries. Excellent negative electrode materials can improve the reversible capacity, rate performance and cycle performance of the battery. At present, the negative electrode material is mainly graphite, whose theoretical specific capacity is only 372mAh / g and the lithium storage capacity is relatively low. In comparison, silicon-based materials have extremely high theoretical specific capacity, and the theoretical specific capacity of silicon is 4200mAh / g. However, silicon-based materials have low electronic conductivity and undergo huge volume changes during the charge and discharge process, resulting in pulverization, which in turn affects the cycle performance of the battery.

[0004] A Chinese patent with publication number CN102891297A discloses a method for preparing a silicon-carbon composite material, wherein graphite, asphalt and nano-silicon are added to an aqueous solution of sodium carboxymethyl cellulose and ball-milled to obtain a nano-scale silicon-carbon composite material precursor; the precursor is then spray-dried and carbonized to obtain a silicon-carbon composite material. Although this method can improve the electrical conductivity through carbon coating, the synthesis process is complicated, and the polymer structure is easily destroyed during the ball milling process, making the slurry system unstable, and the nano-silicon is easy to agglomerate. During the charge and discharge process, there will be excessive local volume expansion and material pulverization, which will lead to poor cycle performance. Summary of the invention

[0005] The object of the present invention is to provide a silicon-carbon composite material and a preparation method and application thereof. The silicon-carbon composite material prepared by the method provided by the present invention has excellent cycle stability.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0008] The nanocellulose solution, the silicon source and the coupling agent are mixed and calcined to obtain the silicon-carbon composite material.

[0009] Preferably, the silicon source comprises elemental silicon and / or SiO x; The value range of x is 0.6~1.4.

[0010] Preferably, the coupling agent includes one or more of a silane coupling agent, a phthalate coupling agent and an aluminate coupling agent.

[0011] Preferably, the mass concentration of the nanocellulose solution is 0.1-50 wt %.

[0012] Preferably, the mass ratio of nanocellulose to coupling agent in the nanocellulose solution is 100:1-50;

[0013] The mass ratio of the nanocellulose to the silicon source in the nanocellulose solution is 1-100:100.

[0014] Preferably, the mixing is carried out under stirring conditions; the stirring speed is 500 rpm and the time is 1 to 10 hours.

[0015] Preferably, the calcination temperature is 600-1300°C and the holding time is 1-4h;

[0016] The calcination is carried out under a protective atmosphere.

[0017] The present invention also provides a silicon-carbon composite material prepared by the preparation method described in the above technical solution, characterized in that the silicon-carbon composite material comprises a silicon-based material and a carbon fiber layer coated on the surface of the silicon-based material.

[0018] Preferably, when the silicon source is SiO x When the silicon-based material comprises elemental silicon and silicon dioxide.

[0019] The present invention also provides the application of the silicon-carbon composite material described in the above technical solution in a lithium battery.

[0020] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps: mixing a nanocellulose solution, a silicon source and a coupling agent, and then calcining to obtain the silicon-carbon composite material. The present invention combines the nanocellulose and the silicon source through a coupling agent, so that the nanocellulose can be tightly wrapped on the surface of the silicon source. During the calcination process, the nanocellulose is carbonized to generate a carbon fiber layer, which is coated on the surface of the silicon-based material. During the charge and discharge process, it can play a good buffering role, reduce the impact of the volume expansion of the silicon-based material, and improve the cycle stability of the silicon-carbon composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a charge and discharge test curve diagram of the composite materials obtained in Examples 1 to 5 and Comparative Example 1 at 0.1C;

[0022] Figure 2It is an AC impedance test curve diagram of the composite materials obtained in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing a silicon-carbon composite material, comprising the following steps:

[0024] The nanocellulose solution, the silicon source and the coupling agent are mixed and calcined to obtain the silicon-carbon composite material.

[0025] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.

[0026] In the present invention, the silicon source preferably includes elemental silicon and / or SiO x In the present invention, the value range of x is preferably 0.6 to 1.4, more preferably 0.7 to 1.3, and more preferably 0.8 to 1.2. In the present invention, the elemental silicon preferably includes micron silicon or nano silicon. In the present invention, the particle size of the micron silicon is preferably 1 to 3 μm; the particle size of the nano silicon is preferably 50 to 200 nm; the SiO x The particle size is preferably 2 to 8 μm.

[0027] In the present invention, the coupling agent preferably includes one or more of a silane coupling agent, a phthalate coupling agent and an aluminate coupling agent. In the present invention, the silane coupling agent is further preferably vinyl trimethoxy silane; the phthalate coupling agent is further preferably a monoalkoxy titanate; and the aluminate coupling agent is further preferably isopropyl distearoyloxy aluminate.

[0028] The present invention has no particular limitation on the type and source of the nanocellulose in the nanocellulose solution, and those familiar to those skilled in the art may be used. In the present invention, the raw materials for preparing the nanocellulose preferably include one or more of wood, cotton, beet, flax, bacteria and microcrystalline cellulose. In the present invention, the method for preparing the nanocellulose preferably includes any one of arc discharge method, laser ablation method, fixed bed catalytic cracking method, acid hydrolysis method and bacterial synthesis method. The present invention has no particular limitation on the specific implementation process of the preparation method, and those familiar to those skilled in the art may be used.

[0029] In the present invention, the nanocellulose solution is preferably obtained by preparation; the preparation method preferably comprises the following steps:

[0030] The nanocellulose and water are mixed to obtain the nanocellulose solution.

[0031] In the present invention, the water is preferably deionized water. In the present invention, the mixing is preferably carried out under stirring; the stirring speed is preferably 500 rpm; the time is preferably 20 to 40 minutes, and more preferably 30 minutes.

[0032] In the present invention, the mixing temperature is preferably 30 to 60° C., more preferably 40 to 50° C. In the present invention, the mixing is preferably performed in a magnetic stirrer with a heating jacket.

[0033] In the present invention, the mass concentration of the nanocellulose solution is 0.1-50wt%, more preferably 1-45%wt%, and more preferably 5-40wt%. In the present invention, the mass ratio of nanocellulose to coupling agent in the nanocellulose solution is preferably 100:1-50, more preferably 100:5-45, and more preferably 100:10-40. In the present invention, the mass ratio of nanocellulose to silicon source in the nanocellulose solution is preferably 1-100:100, more preferably 5-95:100, and more preferably 10-90:100.

[0034] In the present invention, the mixing of the nanocellulose solution, the silicon source and the coupling agent is preferably carried out under stirring; the stirring speed is preferably 200 to 800 rpm, more preferably 400 to 600 rpm, more preferably 500 rpm; the time is preferably 1 to 10 hours, more preferably 2 to 9 hours, more preferably 3 to 8 hours. In the present invention, the mixing is carried out at room temperature. In the present invention, the order of mixing is preferably: adding the silicon source and the coupling agent to the nanocellulose solution. In the present invention, during the above-mentioned mixing process, the coupling agent and nanocellulose are wrapped on the surface of the silicon source.

[0035] After the mixing is completed, the present invention also preferably includes separating and drying the obtained reaction solution. In the present invention, the separation method is preferably centrifugal separation; the rotation speed of the centrifugal separation is preferably 500 to 5000 rpm, more preferably 1000 to 4500 rpm, and more preferably 1500 to 4000 rpm. The present invention has no special limitation on the time and number of centrifugal separation, and those familiar to those skilled in the art can be used.

[0036] In the present invention, the drying temperature is preferably 60 to 120° C., more preferably 70 to 110° C., and more preferably 80 to 100° C. The present invention has no particular limitation on the drying time, as long as a dried product can be obtained. In the present invention, the drying is preferably performed under vacuum conditions.

[0037] In the present invention, the calcination temperature is preferably 600-1300°C, more preferably 700-1200°C, more preferably 800-1000°C; the holding time is preferably 1-4h, more preferably 1.5-3.5h, more preferably 2-3h; the heating rate to the calcination temperature is preferably 5°C / min. In the present invention, the calcination is preferably carried out in a protective atmosphere; the protective atmosphere is preferably nitrogen or argon. In the present invention, the calcination is carried out in a tubular furnace.

[0038] After the calcination is completed, the present invention also preferably includes cooling the obtained product. In the present invention, the cooling process is preferably: reducing the temperature from the calcination temperature to 500°C at a cooling rate of 5°C / min, and then naturally cooling to room temperature.

[0039] The present invention also provides a silicon-carbon composite material prepared by the preparation method described in the above technical solution, wherein the silicon-carbon composite material comprises a silicon-based material and a carbon fiber layer coated on the surface of the silicon-based material.

[0040] In the present invention, the thickness of the carbon fiber layer is preferably 10 to 100 nm.

[0041] In the present invention, when the silicon source is elemental silicon, the silicon-based material preferably includes elemental silicon. x When the silicon-based material is used, the silicon-based material preferably includes elemental silicon and silicon dioxide.

[0042] The present invention also provides the application of the silicon-carbon composite material described in the above technical solution in a lithium battery. The present invention has no special limitation on the specific implementation of the application, and implementations familiar to those skilled in the art can be adopted.

[0043] In order to further illustrate the present invention, a silicon-carbon composite material provided by the present invention and its preparation method and application are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0044] Example 1

[0045] 3 g of nanocellulose and 100 liters of deionized water were stirred at 60° C. and 500 rpm for 30 min to obtain a nanocellulose solution;

[0046] 10g SiO x (D50 particle size is 5 μm, wherein x is 0.8) and 0.5 g of vinyltrimethoxysilane are added to the nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 3 h to mix, and then the obtained mixture is centrifuged at a speed of 3000 rpm, and the obtained precipitate is vacuum dried at 80°C;

[0047] The dried powder was placed in a tubular furnace and calcined at a rate of 5°C / min to 1000°C in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material.

[0048] Example 2

[0049] 1 g of nanocellulose and 100 liters of deionized water were stirred at 60°C and 500 rpm for 30 min to obtain a nanocellulose solution;

[0050] 10 g of SiOx (D50 particle size is 5 μm, where x is 0.8) and 0.5 g of vinyltrimethoxysilane were added to the nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 3 h, and then the obtained mixture was centrifuged at a speed of 3000 rpm, and the obtained precipitate was vacuum dried at 80° C.;

[0051] The dried powder was placed in a tubular furnace and calcined at a rate of 5°C / min to 1000°C in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material.

[0052] Example 3

[0053] 5 g of nanocellulose and 100 liters of deionized water were stirred at 60° C. and 500 rpm for 30 min to obtain a nanocellulose solution;

[0054] 10g SiO x (D50 particle size is 5 μm, wherein x is 0.8) and 0.5 g of vinyltrimethoxysilane are added to the above nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 3 h to mix, and then the obtained mixed solution is centrifuged at a speed of 3000 rpm, and the obtained precipitate is vacuum dried at 80°C;

[0055] The dried powder was placed in a tubular furnace and calcined at a rate of 5°C / min to 1000°C in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material.

[0056] Example 4

[0057] 3 g of nanocellulose and 100 liters of deionized water were stirred at 60° C. and 500 rpm for 30 min to obtain a nanocellulose solution;

[0058] 10g SiO x (D50 particle size is 5 μm, wherein x is 0.8) and 0.5 g of vinyltrimethoxysilane are added to the nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 0.5 h to mix, and then the obtained mixture is centrifuged at a speed of 3000 rpm, and the obtained precipitate is vacuum dried at 80°C;

[0059] The dried powder was placed in a tubular furnace and calcined at a rate of 5°C / min to 1000°C in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material.

[0060] Example 5

[0061] 3 g of nanocellulose and 100 liters of deionized water were stirred at 60° C. and 500 rpm for 30 min to obtain a nanocellulose solution;

[0062] 10g SiO x (D50 particle size is 5 μm, wherein x is 0.8) and 0.5 g of vinyltrimethoxysilane are added to the nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 3 h to mix, and then the obtained mixture is centrifuged at a speed of 3000 rpm, and the obtained precipitate is vacuum dried at 80°C;

[0063] The dried powder was placed in a tubular furnace and calcined at 700°C at a rate of 5°C / min in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material.

[0064] Comparative Example 1

[0065] 10g SiO x (D50 particle size is 5 μm, where x is 0.8), 0.5 g of vinyl trimethoxy silane is added to 100 g of deionized water, stirred at room temperature at a stirring speed of 500 rpm for 3 h, and then the obtained mixture is centrifuged at a speed of 3000 rpm, and the obtained precipitate is vacuum dried at 80°C;

[0066] The dried powder was placed in a tubular furnace and calcined at a rate of 5°C / min to 1000°C in a nitrogen atmosphere for 2 hours. After calcination, the powder was cooled to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain a composite material.

[0067] Performance Testing

[0068] Test Example 1

[0069] A lithium battery was prepared using the composite materials obtained in Examples 1 to 5 and Comparative Example 1 as negative electrode active materials, and the preparation process was as follows: the composite material, carbon black and polyacrylic acid (PAA) were mixed in a mass ratio of 8:1:1, and an appropriate amount of water was added for grinding to obtain an electrode material; then the obtained electrode material was coated on a copper foil by blade coating, and vacuum dried at 80° C. for 12 h to obtain a battery negative electrode;

[0070] In a glove box, the obtained battery negative electrode was used as the working electrode, the lithium metal sheet was used as the counter electrode, 1.0M LiPF6 was used as the electrolyte (the solvent was: ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in equal volume ratio), Celgard 2325 was used as the separator, and they were assembled into a CR2032 button cell. Then, the assembled battery was subjected to charge and discharge cycle test at 0.1C. The test results are shown in Table 1 and Figure 1 shown.

[0071] Table 1 Charge and discharge cycle test results of the composite materials obtained in Examples 1 to 5 and Comparative Example 1

[0072]

[0073] Depend on Figure 1 It can be seen from Table 1 that, compared with the comparative example, the silicon-carbon composite material obtained in the present invention has a higher first coulombic efficiency and better cycle stability.

[0074] Test Example 2

[0075] A lithium battery was prepared using the composite materials obtained in Examples 1 to 5 and Comparative Example 1 as negative electrode active materials, and the preparation process was as follows: the composite material, carbon black and polyacrylic acid (PAA) were mixed in a mass ratio of 91:3:6, and an appropriate amount of water was added for grinding to obtain an electrode material; then the obtained electrode material was coated on a copper foil by blade coating, and vacuum dried at 80° C. for 12 h to obtain a battery negative electrode;

[0076] In a glove box, the obtained battery negative electrode was used as the working electrode, the lithium metal sheet was used as the counter electrode, 1.0M LiPF6 was used as the electrolyte (the solvent was: ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in equal volume ratio), Celgard 2325 was used as the separator, and they were assembled into a CR2032 button cell, and then the assembled battery was subjected to an AC impedance test. The test results are shown in Table 2. The test curves of Examples 1 to 4 and Comparative Example 1 are shown in Table 2. Figure 2 shown.

[0077] Table 2 AC impedance test results of the composite materials obtained in Examples 1 to 5 and Comparative Example 1

[0078] serial number Battery impedance / Ω Example 1 25.2 Example 2 26.0 Example 3 25.1 Example 4 25.5 Example 5 24.8 Comparative Example 1 51.6

[0079] As can be seen from Table 2, the silicon-carbon composite material obtained by the present invention has excellent electrical conductivity;

[0080] In the AC impedance test curve, the arc radius in the high-frequency region represents the diffusion resistance of the electrolyte in the electrode material. The larger the arc radius, the greater the diffusion resistance. Figure 2 It can be seen that in the high-frequency region, the arc radius of the silicon-carbon composite material obtained by the present invention is smaller than that of comparative example 1, indicating that the diffusion internal resistance is smaller than that of comparative example 1; and in the low-frequency region, the curves of embodiments 1 to 4 are closer to being perpendicular to the horizontal axis, indicating that the silicon-carbon composite material obtained by the present invention has higher electrical conductivity.

[0081] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The steps are: 3 g of nanocellulose and 100 liters of deionized water were stirred at 60° C. and 500 rpm for 30 min to obtain a nanocellulose solution; 10g SiO x and 0.5 g of vinyltrimethoxysilane were added to the nanocellulose solution, stirred at room temperature at a stirring speed of 500 rpm for 3 h, and then the obtained mixed solution was centrifuged at a speed of 3000 rpm, and the obtained precipitate was vacuum dried at 80 ° C; the SiO x The particle size of D50 is 5 μm, where x is 0.8; The dried powder was placed in a tubular furnace, heated to 1000°C at a rate of 5°C / min under a nitrogen atmosphere for calcination, and the heat preservation time was 2h. After the calcination was completed, the temperature was reduced to 500°C at a rate of 5°C / min and then naturally cooled to room temperature to obtain the silicon-carbon composite material; The silicon-carbon composite material comprises a silicon-based material and a carbon fiber layer coated on the surface of the silicon-based material; the silicon-based material comprises elemental silicon and silicon dioxide.

Citation Information

Patent Citations

  • Silicon-carbon composite material for lithium ion battery and preparation method thereof

    CN102891297A

  • Silicon-carbon composite material and preparation method thereof

    CN102709536A

  • Three-dimensional silicon-carbon composite negative electrode material and preparation method and application thereof in lithium ion battery

    CN111470486A